2007
DOI: 10.1089/ten.2006.0141
|View full text |Cite
|
Sign up to set email alerts
|

MicroCT Evaluation of Three-Dimensional Mineralization in Response to BMP-2 DosesIn Vitroand in Critical Sized Rat Calvarial Defects

Abstract: Numerous growth factors, peptides, and small molecules are being developed for bone tissue engineering. The optimal dosing, stability, and bioactivity of these biological molecules are likely influenced by the carrier biomaterial. Efficient evaluation of various formulations will require objective evaluation of in vitro culture systems and in vivo regeneration models. The objective of this paper is to examine the utility of microcomputed tomography (microCT) over conventional techniques in the evaluation of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
84
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(92 citation statements)
references
References 49 publications
7
84
1
Order By: Relevance
“…The micro-CT findings were consistent with those of Cowan et al, who found micro-CT was highly accurate in assessing the quality and quantity of defect healing with bone protein in a rat calvarial model [8]. In their study, micro-CT delineated some ultrastructural details of graft incorporation not possible with the histologic technique used, yet a considerable benefit was that the resolution of their micro-CT data was not adversely affected by any artifacts as a result of the presence of metal.…”
Section: Discussionsupporting
confidence: 89%
“…The micro-CT findings were consistent with those of Cowan et al, who found micro-CT was highly accurate in assessing the quality and quantity of defect healing with bone protein in a rat calvarial model [8]. In their study, micro-CT delineated some ultrastructural details of graft incorporation not possible with the histologic technique used, yet a considerable benefit was that the resolution of their micro-CT data was not adversely affected by any artifacts as a result of the presence of metal.…”
Section: Discussionsupporting
confidence: 89%
“…The recommended dose of BMP2 in the manufacturer's instruction is about 400 ng/mm 3 . It was reported that BMP2 could induce bone regeneration in CSD of rat calvaria at the dose of 30 to 240 ng/mm 3,30) . In our previous study, we found that the effective concentration of BMP2/7 to induce osteoblastogenesis was significantly lower than those of BMP2 and BMP7 homodimers 9) .…”
Section: Discussionmentioning
confidence: 99%
“…Bone formation in the calvarial defect model occurs under unloaded conditions. Cowan et al 22) described that recent advances in imaging techniques have been used to assess and characterize fine bony structures such as trabecular bone architecture in vitro and in vivo and that -CT data can accurately substitute for conventional histological sections for bone structure evaluations. Thus, in the present study, CT image analysis was used for new bone formation evaluations.…”
Section: Histological Evaluationmentioning
confidence: 99%